CD4+ T cell surface alpha enolase is lower in older adults. (December 2015) - Bennett, Stuart J.; Augustyniak, Edyta M.; Dunston, Christopher R.; Brown, Richard A.; Shantsila, Eduard; Lip, Gregory Y.H.; Torrao, Rita D.C.; Pararasa, Chathyan; Remtulla, Ali H.; Ladouce, Romain; Friguet, Bertrand; Griffiths, Helen R.
Highlights: α-Enolase is lower on the surface of CD4 + T cell in healthy older adults. Cardiovascular disease patients express less CD4 + T cell α-enolase than age-matched controls. A hypothesis-free proteomic discovery approach has been adopted successfully to study human ageing. Membrane protein enrichment has been developed to reduce bias towards cytosolic protein discovery. Abstract: To identify novel cell ageing markers in order to gain insight into ageing mechanisms, we adopted membrane enrichment and comparison of the CD4 + T cell membrane proteome (purified by cell surface labelling using Sulfo-NHS-SS-Biotin reagent) between healthy young ( n = 9, 20–25 years) and older ( n = 10; 50–70 years) male adults. Following two-dimensional gel electrophoresis (2DE) to separate pooled membrane proteins in triplicates, the identity of protein spots with age-dependent differences ( p < 0.05 and >1.4 fold difference) was determined using liquid chromatography–mass spectrometry (LC–MS/MS). Seventeen protein spot density differences (ten increased and seven decreased in the older adult group) were observed between young and older adults. From spot intensity analysis, CD4 + T cell surface α-enolase was decreased in expression by 1.5 fold in the older age group; this was verified by flow cytometry ( n = 22) and qPCR with significantly lower expression of cellular α-enolase mRNA and protein compared to young adult CD4 + T cells ( p < 0.05). In an independent age-matched case-control study, lower CD4 + T cell surface α-enolase expression was observed in age-matched patients with cardiovascular disease ( p < 0.05). An immune-modulatory role has been proposed for surface α-enolase and our findings of decreased expression suggest that deficits in surface α-enolase merit investigation in the context of immune dysfunction during ageing and vascular disease.